2013
DOI: 10.1007/s12298-013-0178-2
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth stimulation of wheat (Triticum aestivum L.) by inoculation of salinity tolerant Azotobacter strains

Abstract: Five salinity tolerant Azotobacter strains i.e., ST3, ST6, ST9, ST17 and ST24 were obtained from saline soils. These Azotobacter strains were used as inoculant for wheat variety WH157 in earthen pots containing saline soil under pot house conditions, using three fertilizer treatment doses i.e., control (no fertilizer, no inoculation), 90 Kg N ha(-1) and 120 Kg N ha(-1). Inoculation with salinity tolerant Azotobacter strains caused significant increase in total nitrogen, biomass and grain yield of wheat. Maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…The chlorophyll and the potassium contents were improved while the concentrations of amino acids, proline and sodium were reduced. These results were reported by many authors (Nadeem et al, 2006;Chaudhary et al, 2013). According to Glick et al (1998), the use of PGPR (for example, Pseudomonas) as inoculant of wheat seeds in saline soils improved the plant height, root length, the grain yield, chlorophyll content and the ratio K + /Na + .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The chlorophyll and the potassium contents were improved while the concentrations of amino acids, proline and sodium were reduced. These results were reported by many authors (Nadeem et al, 2006;Chaudhary et al, 2013). According to Glick et al (1998), the use of PGPR (for example, Pseudomonas) as inoculant of wheat seeds in saline soils improved the plant height, root length, the grain yield, chlorophyll content and the ratio K + /Na + .…”
Section: Discussionsupporting
confidence: 69%
“…According to Glick et al (1998), the use of PGPR (for example, Pseudomonas) as inoculant of wheat seeds in saline soils improved the plant height, root length, the grain yield, chlorophyll content and the ratio K + /Na + . The role of Azotobacter in the production of growth-promoting substances and plant improving resistance to abiotic and biotic stresses must also be considered (Chaudhary et al, 2013;Sahoo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Inoculation of maize with Azotobacter strains has been shown to have general positive effects under saline stress by facilitating uptake of K + and exclusion of Na + as well as increasing phosphorous and nitrogen availability [24]. In wheat, inoculation of salt tolerance Azobacter strains increased biomass, nitrogen content, and grain yield under salt stress [25].…”
Section: Microorganisms Affecting Stress Tolerancementioning
confidence: 99%
“…These strains were inoculated in earthen pots containing saline soil under greenhouse conditions. The results of rhizosphere soil monitoring showed that the concentration of the inoculated strains increased up to 60 days of sampling (Chaudhary et al, 2013; Table 1). However, this approach did not allow the identification of microorganisms present in the culture at genus and species level in nonsterile condition.…”
Section: Greenhousementioning
confidence: 99%